Stream Bank Plantations - Murthy, V.V.N. (Journal of Soil and Water Conservation, 2022)
All rivers and streams while following through hilly rigions or alluvial plains have a tendency to erode away their banks. Crop lands, village and urban areas situated on the stream banks are continuously threatened by erosion and sometimes destroyed during the course of floods without any warning. Over the long stretches of the stream banks valuable trees are continuously uprooted. At some place; this stream bank erosion threatens the existence of bridges and culverts built across the stream.